2000
DOI: 10.1097/00006123-200008000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Management of Severe Traumatic Brain Injury by Decompressive Craniectomy

Abstract: Although there was a significant decrease in midline shift after craniectomy, this did not translate into decompressive craniectomy demonstrating a beneficial effect on patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
178
1
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(198 citation statements)
references
References 42 publications
8
178
1
8
Order By: Relevance
“…The outcome of BDC varies form one report to another [3, 6, 13, 14, 15, 16, 17, 18, 19], this difference in outcome could be attributed to the amount of primary brain damage, the neurological status (GCS) after resuscitation and the timing of surgery. Despite severe brain damage seen in her preoperative scan (which made survival unlikely) our patient had surprisingly made a quite rapid recovery to Glasgow outcome score 3 in 10 weeks time.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of BDC varies form one report to another [3, 6, 13, 14, 15, 16, 17, 18, 19], this difference in outcome could be attributed to the amount of primary brain damage, the neurological status (GCS) after resuscitation and the timing of surgery. Despite severe brain damage seen in her preoperative scan (which made survival unlikely) our patient had surprisingly made a quite rapid recovery to Glasgow outcome score 3 in 10 weeks time.…”
Section: Discussionmentioning
confidence: 99%
“…Whitfield et al [122] reported beneficial effects of decompression also on other ICP variables, such as ICP waveform, the magnitude of slow ICP waves, and the correlation coefficient between ICP amplitude and ICP; CPP, however, was not affected. Examining the effects of the procedure on CT appearance, a decrease in midline shift and improved visibility of the mesencephalic cisterns were observed as a result of decompression [81].…”
Section: Decompressive Craniectomymentioning
confidence: 99%
“…In both animal and human studies, surgical decompression has been found to lower ICP by increasing intracranial volume [4,7,25,38,41,42,44,47,54,61,78,89]. Muench et al [81] found that the mean volume gained by surgical decompression ranged from 15.9 to 347.4 cm 3 with a median volume of 73.6 cm 3 . In subtemporal craniectomy without opening the dura, Alexander et al [4] measured a gain of 30 cm 3 in volume.…”
Section: Decompressive Craniectomymentioning
confidence: 99%
See 1 more Smart Citation
“…[1,4,5]. Основным механизмом дей-ствия декомпрессии является создание дополни-тельного пространства для компенсации увеличен-ного внутричерепного объема [6][7][8]11]. Считается, что эффективность декомпрессии зависит от разме-ра декомпрессионного окна [9][10][11].…”
unclassified